On the Relationship between Changes in the Deep Veins Evaluated by Duplex Sonography and the Postthrombotic Syndrome 12 Years after Deep Vein Thrombosis - Franzeck, U K; Schalch, I; Bollinger, A (Thrombosis and Haemostasis, 1997)
In a prospective study we performed color duplex ultrasonography to evaluate patency and valvular function of previous thrombosed veins 12 years after the acute thrombosis.Normal clinical findings were found in 64% of the patients, mild postthrombotic skin changes in 28%, and marked trophic changes in 5%; only 1 venous ulcer occurred.In 39 patients, 114 initially thrombosed vein segments were evaluated. Thirty-seven of 72 proximal segments were completely recanalized (23 with valvular incompetence) and 21 segments exhibited partial recanalization (19 with valvular incompetence). Superficial femoral vein segments were completely occluded in 19%, however, excellent collateralization was provided via the deep femoral vein. Thromboses of the posterior tibial vein demonstrated a high rate of recanalization with development of valvular incompetence in 52%.Whereas obstruction and valvular incompetence as single factors led to a postthrombotic leg in 8.5% and 33%, respectively, the most frequent cause for the development of the postthrombotic syndrome was the combination of reflux plus obstruction in the deep veins (50%).Compression therapy with elastic compression stockings is recommended for at least 5 years after the acute thrombosis.